Measuring and Comparing Aggregation Inconsistency for Chinese Titles in Two Library Catalogues - Arsenault, Clément (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
When recording titles in vernacular Chinese characters or in their Romanized form, either a monosyllabic pattern or a polysyllabic pattern can be followed. Previous research has shown that polysyllabic transcription helps reduce ambiguity and tends to increase precision in retrieval. As there are no clear cut rules as to how syllables should be aggregated into lexical units, polysyllabic entries are a potential source of inconsistency in a bibliographic database. The aim of this study is to investigate the inconsistencies in the aggregation of Chinese characters (i.e., syllables) into lexical words in the bibliographic records of two library catalogues. Over 5,000 records from the East Asian Library at Université de Montréal (CETASE) and 5,000 records from the Library of Congress (LC) were analysed and tested for aggregation consistency. Detailed analysis reveals fairly high consistency levels in both sets. Lors de l’enregistrement des titres en caractères chinois vernaculaires ou sous leur forme romanisée, un modèle monosyllabique ou polysyllabique peut être utilisé. Des recherches antérieures ont démontré que la transcription en polysyllabes atténue les ambiguïtés et tend à améliorer la précision lors du repérage. Puisqu’il n’existe aucune règle fermement établie sur la manière avec laquelle les syllabes doivent être agrégées en unités lexicales, la transcription polysyllabique est une source potentielle d’inconsistance dans les bases de données bibliographiques. Le but de cette étude est d’examiner l’inconsistance dans l’agrégation des caractères chinois (c’est-à-dire des syllabes) des mots lexicaux contenus dans les notices bibliographiques de deux catalogues de bibliothèques. Plus de 5 000 notices du Centre d’études de l’Asie de l’Est de l’Université de Montréal (CETASE) et 5 000 notices de la Library of Congress (LC) ont été analysées et la consistance de l’agrégation a été vérifiée. Une analyse détaillée révèle des niveaux de consistance élevés pour les deux ensembles.